RUSSIAN SCHOOL OF BOOK SCIENCE IN THE FIRST THREE DECADES OF THE 20th CENTURY - LELIKOVA, NATALIJA (Knygotyra, 2015)
The period of 1920s appears as the most fruitfull phase of book science in Russia, involving a series of bibliological systems by N.M. Lisovsky, A.M. Loviagin, M.N. Kufaev, A.A. Sidorov, M. I. Shelkunov, A.G. Fomin, N.M. Somov, etc. The three first decades in Russia offered conceptual research emphasizing the historical and sociological values of Book; evolutionary nature both of the Book as a whole and its various elements was postulated. However, with book science in the USSR reformed along the principles of Marxist ideology in the 1930s, methodological and theoretical investigations of Russian scientists gave way to routine ideological focuses on class character of Book. It was not until late 1950s when book science was re-established in Russia.